Capacitive electrode sensor implanted on a printed circuit board designed for continuous water level measurement - Salami Ifedapo Abdullahi; Mohamed Hadi Habaebi; Noreha Abdul Malik (Institute of Advanced Engineering and Science, 2019)
Water level sensors are one of the practical ways to get the actual measurement of the depth of a dam or canal. The ease of deployment and easy data acquisition makes them widely used in many fields. Therefore, it will be advantageous to have a miniaturized water level sensor for easier mobility and deployment. A novel method for measuring water level using a Printed Circuit Board has been proposed in this paper. The design stages of circuit sketching, printing of sketch on PCB and etching are discussed for the electrode water level sensor. A signal conditioning circuit is necessary to maintain a steady flow of current from the power source. The fabricated electrode water level sensor was tested based on its capacitive effect while charging up and the amount of current at each electrode finger at the saturation stage. The hardware enablers for this test were the multimeter and LCR meter. Arduino microprocessor was used to test and measure the transient response time for each electrode finger. The transient response sensitivity of the electrode sensor is measured to be 0.0873 millisecond/cm while the resolution of the electrode sensor is 0.1cm over a range of 30cm water level. A multiple correlation of 0.921 was achieved for the water level, measured current and measured capacitance with P-values less than 0.05 indicating strength of the data obtained from the tests conducted. The result showed strong evidence that the electrode water level sensor can be an alternative method of measuring water level.